2016
DOI: 10.1016/j.neuroimage.2015.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal bases of structural coherence in contemporary dance observation

Abstract: The neuronal processes underlying dance observation have been the focus of an increasing number of brain imaging studies over the past decade. However, the existing literature mainly dealt with effects of motor and visual expertise, whereas the neural and cognitive mechanisms that underlie the interpretation of dance choreographies remained unexplored. Hence, much attention has been given to the action observation network (AON) whereas the role of other potentially relevant neuro-cognitive mechanisms such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Both factors may have contributed to their greater recruitment during sign language processing. Some researchers have proposed that there may be common processes shared by biological motion and language perception, notably the integration of information over time and space (Redcay, 2008; Bachrach et al, 2016). If activations in the pSTS and TPJ reflect the integration of words into a larger context, the fact that these regions respond more strongly to sign language in all conditions of our study suggests that integration occurs in sign language even at the level of a single sign.…”
Section: Discussionmentioning
confidence: 99%
“…Both factors may have contributed to their greater recruitment during sign language processing. Some researchers have proposed that there may be common processes shared by biological motion and language perception, notably the integration of information over time and space (Redcay, 2008; Bachrach et al, 2016). If activations in the pSTS and TPJ reflect the integration of words into a larger context, the fact that these regions respond more strongly to sign language in all conditions of our study suggests that integration occurs in sign language even at the level of a single sign.…”
Section: Discussionmentioning
confidence: 99%
“…Brain activation related to event segmentation has also been revealed in dance-like actions (Schiffer and Schubotz, 2011; Pollick et al, 2012; Noble et al, 2014; Bachrach et al, 2016, i.a.). Furthermore, some studies based on artificial grammar learning show that humans can implicitly learn regularities in the structure of dance steps (Opacic et al, 2009, i.a.).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Rehfeld and his colleagues found that an 18-month dance training induced an increased hippocampal volume and higher balance function [16]. Another study reported that language processing and dance watching might share certain neural mechanisms and dance training might affect the syntax ability [17]. Fink and his colleagues discovered stronger alpha synchronization in dancers during high creative thinking compared with controls [18].…”
Section: Introductionmentioning
confidence: 99%